The Development of Publications on Catheter-Related Bladder Discomfort: A Bibliometric Analysis - Jiang W; Chen X; Peng Y; Zhai W; Zhang X; Zhou Y; Zhou R (Therapeutics and Clinical Risk Management)
Wencai Jiang,1 Xuemeng Chen,1 Yanhua Peng,1 Wenhu Zhai,1 Xianjie Zhang,1 Yukai Zhou,1 Rui Zhou2 1Department of Anesthesiology, Deyang People’s Hospital, Deyang, 618000, People’s Republic of China; 2Shanghai Key Laboratory of Anesthesiology and Brain Functional Modulation, Clinical Research Center for Anesthesiology and Perioperative Medicine, Translational Research Institute of Brain and Brain-Like Intelligence, Department of Anesthesiology and Perioperative Medicine, Shanghai Fourth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200434, People’s Republic of ChinaCorrespondence: Rui Zhou, Shanghai Fourth People’s Hospital, No. 1279, Sanmen Road, Shanghai, 200434, People’s Republic of China, Email ruizhoukepler@126.comBackground: Catheter-related bladder discomfort (CRBD) is a risk factor that impacts postoperative recovery and still troubles patients and healthcare staff. The present study is a bibliometric analysis of CRBD.Methods: The publications on CRBD were retrieved from the Web of Science Core Collection. VOSviewer and Excel were applied to present the current status and hot spots of CRBD research. We analyzed parameters such as the annual number of publications, countries/regions, organizations, authors, journals, and keywords of the articles in this area by generating visualization graphs.Results: A total of 127 articles were eligible, recorded by 78 journals, and drafted by 672 authors from 169 organizations in 26 countries/regions. The main type of these articles is randomized trial. Park Hee-Pyoung, Kim Hyun-Chang, and Cui Yuanshan are the most productive authors with 5 articles. Sichuan University, Seoul National University, Sanjay Gandhi Post Graduate Institute of Medical Sciences, Capital Medical University, and Qingdao University published more articles on CRBD worldwide. China ranks No. 1 in terms of the number of publications, followed by South Korea and India. Journals specialized in anesthesiology, such as BMC Anesthesiology, Journal of Anesthesia, and British Journal of Anesthesia, are more popular with researchers in this area. The research hot spots of CRBD have concentrated on the prevention and treatment of CRBD.Conclusion: Though formal research on CRBD started late, there is a rising tendency for the number of publications. Authors and academic teams from Asia have made significant contribution to CRBD. Journals specialized in anesthesiology are priorities for publishing articles. Previous studies mainly focused on the pharmacological and pharmacological methods to CRBD. However, CRBD is not fully settled. Either clinical or experimental studies are still needed to further improve CRBD.Keywords: catheter-related bladder discomfort, CRBD, bibliometric analysis, hot spots